ТОЙ – ТӘРБИЯ ҚУРАЛЫ СЫПАТЫНДА - Пазылов, А. (ILIM hám JÁMIYET, 2017)
The article is dedicated to the description of one of the main national customs of our people- weddings. In the article the author tells his opinion about upbringing points of national weddings, where grown- ups with their manners of behaviour show the model to young generation, about negative sides of luxurious weddings and the importance of service at wedding parties